1970
DOI: 10.3126/jcmsn.v6i2.3609
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Neonatal sepsis

Abstract: Objective: To study the clinical presentation, investigational profile and outcome of neonatal sepsis in general and with special reference to inborn (intramural) or out born (extramural), sex and weight of the neonate. Materials and method: Retrospective descriptive study of neonates admitted during 2 years from July 2007 to June 2009 in special care neonatal unit of the department of Pediatrics, College of Medical Sciences-Teaching Hospital, Bharatpur, Nepal. Results: Majority of neonates were out born and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 3 publications
7
19
0
1
Order By: Relevance
“…Although no plausible mechanism has been proposed for the male preponderance of acute febrile encephalopathy, it may possibly be because of the gender biasness in seeking medical care especially in this part of the world. As noted by Khinchi et al from Nepal, this study also revealed increased number of cases during the monsoon season of July to August which may be due to the increase transmission of the diseases during the monsoon months 13 . Similarly acute febrile encephalopathy was found to occur more frequently in people of low socioeconomic status in our country, present in 32 (59%) children, which was similar to that noted in India 10 and to correlate clinical and radiological features of pa ents with viral encephali s.\n\nMETHODS: A prospec ve hospital based study conducted on the consecu ve pa ents admi ed in a pediatric unit during the period of 1(st.…”
Section: Discussionsupporting
confidence: 78%
“…Although no plausible mechanism has been proposed for the male preponderance of acute febrile encephalopathy, it may possibly be because of the gender biasness in seeking medical care especially in this part of the world. As noted by Khinchi et al from Nepal, this study also revealed increased number of cases during the monsoon season of July to August which may be due to the increase transmission of the diseases during the monsoon months 13 . Similarly acute febrile encephalopathy was found to occur more frequently in people of low socioeconomic status in our country, present in 32 (59%) children, which was similar to that noted in India 10 and to correlate clinical and radiological features of pa ents with viral encephali s.\n\nMETHODS: A prospec ve hospital based study conducted on the consecu ve pa ents admi ed in a pediatric unit during the period of 1(st.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have thrown light the reliability of procalcitonin in the diagnosis of neonatal sepsis, particularly in distinguishing causative agents, proving its value in excluding bacterial infections, with a negative predictive value of 93% [17][18]. Demographically, male children (61.3%) were more affected in our study, similar to the available reports (62.4%-65.9%) [19][20][21]. There is a genetic linking to the x-linked immuno-regulatory gene resulting in the host's susceptibility to the infection in males [22].…”
Section: Discussionsupporting
confidence: 86%
“…One of the Millennium Development Goals is to reduce the number of deaths in children under 5 years to two third by the year 2015, and to achieve this goal a substantial reduction in neonatal deaths will be required especially in the developing countries 4 . In the developed countries, the main cause of morbidity and mortality in the neonatal period is congenital abnormalities which are mostly non-preventable, but in the developing countries the common causes such as infections, jaundice, birth asphyxia and pneumonia predominate 5 . The neonatal disease pattern is a sensitive indicator of availability, utilization and effectiveness of mother and child health services in the community.…”
Section: Introductionmentioning
confidence: 99%